Coronary Heart Disease and an Incidental Parathyroid Carcinoma - M. Stoll; C. A. Nebiker; L. Remonda; R. Grobholz (Case Reports in Pathology)
A 71-year-old woman was admitted with angina pectoris. During hospitalization she developed a myocardial infarction (NSTEMI). Laboratory results revealed a mild elevated troponin and an elevated calcium level (3.35 mmol/l). Subsequently, there was a decreased phosphate (0.36 mmol/l [normal 0.81-1.62 mmol/l]) as well as 16-fold elevated serum level of parathyroid hormone (PTH, 1156 ng/l [normal 10-73 ng/l]), indicating a primary hyperparathyroidism. Sonographically a thyroidal node was detected, not clearly demarcated (TIRADS 5). FNA showed a monomorphic, partial follicular cell population with an immunohistochemical positivity for PTH. Magnetic resonance imaging (MRI) showed a 5 cm large tumor at the right caudal pole of the thyroid with compression of the dorsolateral trachea without infiltration. Surgical removal with en bloc resection of the right hemithyroid with parathyroidectomy was performed. Postoperatively the PTH level dropped to 12.1 ng/l. Pathological examination revealed a 5 cm tumor with infiltration of the thyroid and a perineural invasion. The diagnosis of a presymptomatic parathyroid carcinoma could be established. The affirmative histopathological diagnosis of a parathyroid carcinoma can be challenging and is limited to tumors with evidence of invasive growth in adjacent structures such as the thyroid and/or soft tissue, perineural spaces, angioinvasion of capsular and/or extracapsular vessels, and/or documented metastases.